Teacher Innovation to Facilitate Student Learning Experiences in Building Construction Cost Estimation Learning - Lutfiana, Riza Nur Dwi; Siregar, Eveline; Winarsih, Murni (LPPM Undiksha, 2022)
The construction and property business expertise program have obstacles in learning activities for Construction and Property Cost Estimation, namely the lack of face-to-face time in class. In addition, the limitations of space and the density of material cause learning activities not to run optimally. This study aims to create an enriched virtual classroom with a STAD approach on the subject of Construction Cost Estimation. This research is development research (R&D) and uses the PEDATI model in designing learning. The subjects of this study were 59 students who took Cost and Construction Estimates. The methods used to collect data are observation, interviews, and questionnaires. The instrument used to collect data is a questionnaire. The data analysis technique used is descriptive qualitative and quantitative analysis techniques. The results of the study resulted in an enriched virtual classroom learning design. Material selection, STAD discussion forms, assignments, and evaluation forms are arranged in such a way and combined with the LMS used. With the enriched virtual classroom, learning will be more varied to enrich the student learning experience.